D-galacto-D-mannan-mediated Dectin-2 activation orchestrates potent cellular and humoral immunity as a viral vaccine adjuvant - Kim, Hyeong Won; Ko, Mi-Kyeong; Park, So Hui; Shin, Seokwon; Kim, Gang Sik; Kwak, Dong Yun; Park, Jong-Hyeon; Kim, Su-Mi; Lee, Jong-Soo; Lee, Min Ja (Frontiers in Immunology, 2024)
Introduction: Conventional foot-and-mouth disease (FMD) vaccines have been developed to enhance their effectiveness; however, several drawbacks remain, such as slow induction of antibody titers, short-lived immune response, and local side effects at the vaccination site. Therefore, we created a novel FMD vaccine that simultaneously induces cellular and humoral immune responses using the Dectin-2 agonist, D-galacto-D-mannan as an adjuvant.We evaluated the innate and adaptive (cellular and humoral) immune responses elicited by the novel FMD vaccine and elucidated the signaling pathway involved both in vitro and in vivo using mice and pigs, as well as immune cells derived from these animals.Results: D-galacto-D-mannan elicited early, mid-, and long-term immunity via simultaneous induction of cellular and humoral immune responses by promoting the expression of immunoregulatory molecules. D-galacto-D-mannan also enhanced the immune response and coordinated vaccine-mediated immune response by suppressing genes associated with excessive inflammatory responses, such as nuclear factor kappa B, via Sirtuin 1 expression.Our findings elucidated the immunological mechanisms induced by D-galacto-Dmannan, suggesting a background for the robust cellular and humoral immune responses induced by FMD vaccines containing D-galacto-D-mannan. Our study will help to facilitate the improvement of conventional FMD vaccines and the design of next-generation FMD vaccines.